REGULATORY AND LEGAL REGULATION OF THE ACTIVITIES OF "DRY PORTS" (Development Service Industry Management, 2023)
In the context of the long-term large-scale war launched by Russia against Ukraine, the issue of studying the regulatory and legal support for the creation and operation of "dry ports" in Ukraine, which are almost the only alternative for container transportation, is of particular relevance. It is worth noting that the legal status and activities of "dry ports" in our country are not separately regulated. Currently, the legislation does not define the essence, functional load, features of the creation and operation of logistics hubs of this type, which leads to significant legal conflicts and difficulties in identifying them and regulating their activities.The article is devoted to the study of the regulatory and legal regulation of the functioning of "dry ports". An overview of the main regulatory documents that reveal the issue of multimodal transportation is provided. Collision issues of the domestic practice of normalization of the activity of "dry ports" and problematic issues and directions for their improvement in the context of finalization of the domestic regulatory and legal framework on the investigated issue are outlined.The author notes that in domestic legislation, the concepts of “multimodal transportation” and “combined transportation” are used in parallel, in some cases the category of “mixed transportation” is also used, which, taking into account their content, should be considered identical, while in European legislation, attention is focused more on combined transportation. At the same time, only the Law of Ukraine “On Multimodal Transportation” provides a definition and features of the organization and functioning of multimodal terminals, which, according to the logic of the legislative initiative, should be understood as “dry ports”. However, taking into account the study of international experience indicates the presence of significant differences between these types of logistics facilities. It is also worth noting that the Customs Code of Ukraine does not contain definitions of these concepts.
Keywords: port; dry port; multimodal transportation; intermodal transportation; mixed transportation